A Personal Respirator to Improve Protection for Healthcare Workers Treating COVID-19 (PeRSo) - Elkington, Paul T.; Dickinson, Alexander S.; Mavrogordato, Mark N.; Spencer, Daniel C.; Gillams, Richard J.; De Grazia, Antonio; Rosini, Sebastian; Garay-Baquero, Diana J.; Diment, Laura E.; Mahobia, Nitin; Mant, Alexandra; Baynham, Tom; et al. (Frontiers in Medical Technology, 2021)
Introduction: SARS-CoV-2 infection is a global pandemic. Personal Protective Equipment (PPE) to protect healthcare workers has been a recurrent challenge in terms of global stocks, supply logistics and suitability. Around 20% of healthcare workers treating COVID-19 cases have become infected, which leads to staff absence at peaks of the pandemic, and in some cases mortality. Methods: To address current shortcomings in PPE, we developed a simple powered air purifying respirator, made from inexpensive and widely available components. The prototype was designed to minimise manufacturing complexity so that derivative versions could be developed in low resource settings with minor modification. Results: The “Personal Respirator – Southampton” (PeRSo) delivers High-Efficiency Particulate Air (HEPA) filtered air from a battery powered fan-filter assembly into a lightweight hood with a clear visor that can be comfortably worn for several hours. Validation testing demonstrates that the prototype removes microbes, avoids excessive CO2 build-up in normal use, and passes fit test protocols widely used to evaluate standard N95/FFP2 and N99/FFP3 face masks. Feedback from doctors and nurses indicate the PeRSo prototype was preferred to standard FFP2 and FFP3 masks, being more comfortable and reducing the time and risk of recurrently changing PPE. Patients report better communication and reassurance as the entire face is visible. Conclusion: Rapid upscale of production of cheaply produced powered air purifying respirators, designed to achieve regulatory approval in the country of production, could protect healthcare workers from infection and improve healthcare delivery during the COVID-19 pandemic.